Neonatal screening: 9% of children with filter paper thyroid-stimulating hormone levels between 5 and 10 μIU/mL have congenital hypothyroidism - Flávia C. Christensen-Adad; Carolina T. Mendes-; Maura M.F. Goto; Letícia E. Sewaybricker; Lília F.R. D'Souza-Li; Gil Guerra-Junior; André M. Morcillo; Sofia Helena V. Lemos-Marini (Elsevier, 2017)
Objectives: To determine the prevalence of congenital hypothyroidism in children with filter-paper blood-spot TSH (b-TSH) between 5 and 10 μIU/mL in the neonatal screening. Methods: This was a retrospective study including children screened from 2003 to 2010, with b-TSH levels between 5 and 10 μIU/mL, who were followed-up during the first two years of life when there was no serum TSH normalization. The diagnosis of congenital hypothyroidism was defined as serum TSH ≥10 μIU/mL and start of levothyroxine treatment up to 2 years of age. Results: Of the 380,741 live births, 3713 (1.04%) had filter paper TSH levels between 5 and 10 μIU/mL and, of these, 339 (9.13%) had congenital hypothyroidism. Of these, 76.11% of the cases were diagnosed in the first three months of life and 7.96% between 1 and 2 years of age. Conclusion: The study showed that 9.13% of the children with b-TSH levels between 5 and 10 μIU/mL developed hypothyroidism and that in approximately one-quarter of them, the diagnosis was confirmed only after the third month of life. Based on these findings, the authors suggest the use of a 5 μIU/mL cutoff for b-TSH levels and long-term follow-up of infants whose serum TSH has not normalized to rule out congenital hypothyroidism. Resumo: Objetivos: Determinar a prevalência de hipotireoidismo congênito em crianças com TSH em papel filtro (TSH-f) entre 5 e 10 μUI/mL na triagem neonatal. Métodos: Estudo retrospectivo incluindo crianças triadas de 2003 a 2010, com TSH-f entre 5 e 10 μUI/mL, que foram acompanhadas nos dois primeiros anos de vida quando não houve normalização do TSH sérico. O diagnóstico de hipotireoidismo congênito foi definido como TSH sérico igual ou superior a 10 μUI/mL e início de tratamento com levotiroxina até os dois anos de idade. Resultados: Dos 380.741 nascidos vivos triados, 3.713 (1,04%) apresentaram TSH-f entre 5 e 10 μUI/mL e, destes, 339 (9,13%) tinham hipotireoidismo congênito. Destes, 76,11% dos casos foram diagnosticados nos primeiros três meses de vida e 7,96% entre um e dois anos de idade. Conclusão: O estudo mostra que 9,13% das crianças com TSH-f entre 5 e 10 μUI/mL desenvolveram hipotireoidismo e que em cerca de um quarto delas o diagnóstico só se confirmou após o terceiro mês de vida. Com base nestes achados, sugere-se a utilização do ponto de corte de TSH-f de 5 μUI/mL e o acompanhamento em longo prazo dos lactentes cujo TSH sérico não tenha se normalizado para descartar o hipotireoidismo congênito. Keywords: Congenital hypothyroidism, Neonatal screening, Infant, Newborn, Thyroid diseases, Palavras-chave: Hipotireoidismo congênito, Triagem neonatal, Lactente, Recém-nascido, Doenças da glândula tireoide